Impact of Different Acid Extraction Conditions on Physicochemical Properties, Structures and Hypoglycemic Activity of Large-Leaf Yellow Tea Polysaccharides - XUAN Kaili, CHEN Hao, WANG Zhuang, WANG Mengqi, WANG Zhenghang, ZHOU Xinyu, YANG Yue, CHEN Yan (Shipin Kexue, 2025)
This study aimed to investigate the effects of different acid extraction conditions on the structures and biological activities of large-leaf yellow tea polysaccharides. Six polysaccharides, namely LTP-1, LTP-2, LTP-3, LTP-4, LTP-5 and LWTP, were respectively extracted from large-leaf yellow tea by hydrochloric acid solutions at pH levels of 1, 2, 3, 4 and 5 and water. Their physicochemical properties, molecular structures, and hypoglycemic activities were evaluated. The results indicated that the chemical and monosaccharide compositions of LTPs significantly differed from those of LWTP. The contents of total sugar and uronic acids in LTPs were higher than those in LWTP, with a 2.25- and 2.91-fold increase being found in LTP-2 relative to LWTP, respectively. The galacturonic acid contents in LTP-2, LTP-3, and LTP-4 increased by 87.93%, 44.49%, and 6.49%, respectively, compared with that in LWTP, while those in LTP-1and LTP-5 decreased by 14.14% and 34.89%, respectively. Animal experiments demonstrated that LTPs effectively reduced glycated hemoglobin (HbA1c) levels and insulin resistance, and alleviated abnormal lipid metabolism in a mouse model of type 2 diabetes mellitus (T2DM), with LTP-2 exhibiting the best hypoglycemic effect. In conclusion, acid extraction significantly modified the physicochemical properties of large-leaf yellow tea polysaccharide, leading to an increased content of acidic sugars, alterations in molecular structures, and enhanced hypoglycemic activity. This study provides preliminary insights into the complex relationship between structural changes of large-leaf yellow tea polysaccharides before and after hydrochloric acid treatment and their biological activities. These findings lay a theoretical foundation for future investigation into the structure-activity relationships and mechanisms of action of large-leaf yellow tea polysaccharides.